Role of estrogen receptors in the regulation of reactive gliosis - Luis Miguel Garcia-Segura; Inigo Azcoitia; George E. Barreto (Frontiers in Cellular Neuroscience, 2015)
Although estradiol may directly act on neurons to promote neuroprotection in vitro, the participation of other cell types is also necessary to maintain global tissue homeostasis in vivo (Arevalo et al., 2010; Johann and Beyer, 2013; Acaz-Fonseca et al., 2014). Thus, estradiol acts on glial and endothelial cells to maintain the function of the neurovascular unit, regulates gliosis and the inflammatory response of astrocytes and microglia to control neuroinflammation and acts on neurons, astrocytes and oligodendrocytes to maintain the function and propagating properties of neuronal circuits (Garcia-Ovejero et al., 2005; Tapia-Gonzalez et al., 2008; Barrerto et al., 2009; Cerciat et al., 2010; López Rodríguez et al., 2011; Barreto et al., 2014). Glial cells express estrogen receptors (ERs), including ERalpha, ERbeta and G protein-coupled estrogen receptor-1 (GPER) (Garcia-Ovjero et al., 2005; Dhandapani and Brann, 2007) and brain injury induces both the synthesis of estradiol in both reactive astrocytes and the expression of ERs in these cells (Garcia-Ovejero et al., 2002). This suggests that astrocytes may play an important role in the neuroprotective actions of estradiol. Indeed, recent studies, using conditional KO mice for ERalpha and ERbeta, have shown that in an experimental model of multiple sclerosis the protective action of estradiol is mediated by ERalpha expressed in astrocytes, but not by ERalpha expressed in neurons or ERbeta expressed in astrocytes or neurons (Spence et al., 2013).